2022
DOI: 10.3390/biom12010070
|View full text |Cite
|
Sign up to set email alerts
|

Association between Soluble α-Klotho Protein and Metabolic Syndrome in the Adult Population

Abstract: Klotho protein is an anti-aging protein and plays multiple roles in ion-regulation, anti-oxidative stress, and energy metabolism through various pathways. Metabolic syndrome is a combination of multiple conditions that compose of multiple risk factors of cardiovascular disease and type 2 diabetes. Gene regulation and protein expression are discovered associated with metabolic syndrome. We aimed to figure out the correlation between Klotho protein and metabolic syndrome in generally healthy adults. A cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Furthermore, this study also demonstrated that obesity may be closely related to serum alpha-Klotho levels (beta coefficient, 95% confidence interval: 0.66, 0.2-1.11, p=0.005) (1). The close relationship of obesity and serum alpha-Klotho has also been reported in a previous study (5). Therefore, the effect of obesity on the results of this study cannot be ruled out.…”
Section: Sirssupporting
confidence: 65%
“…Furthermore, this study also demonstrated that obesity may be closely related to serum alpha-Klotho levels (beta coefficient, 95% confidence interval: 0.66, 0.2-1.11, p=0.005) (1). The close relationship of obesity and serum alpha-Klotho has also been reported in a previous study (5). Therefore, the effect of obesity on the results of this study cannot be ruled out.…”
Section: Sirssupporting
confidence: 65%
“…Likewise, serum klotho levels were negatively correlated with waist circumference and BMI among women aged 19–33 years with polycystic ovary syndrome [ 15 ]. A recent large analysis of the NHANES also demonstrated significantly lower serum klotho levels among participants with abdominal obesity than those without [ 16 ]. The present results extend those from previous research by reporting that prevalent general and abdominal obesity were significantly associated with lower klotho levels only in women.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, young Japanese women with restrictive-type anorexia nervosa or obesity had significantly lower serum klotho levels than those with a healthy body weight [14]. Recent studies also demonstrated that serum klotho levels were negatively correlated with waist circumference in young women with polycystic ovary syndrome and among community-dwelling adults with abdominal obesity [15][16][17]. Whether the obesity history is associated with lower klotho levels has not been previously explored.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, increased levels of Klotho reduce oxidative damage after myocardial infarction in animal models 40 . Furthermore, reduced Klotho levels are also associated with central obesity, elevated triglycerides, and metabolic syndrome 41 . Not surprisingly, reduced Klotho levels and elevated FGF23 concentrations have been associated with increased hospitalizations for heart failure and the incidence of cardiovascular death in a population of 3555 patients with stable ischemic heart disease 42 .…”
Section: Discussionmentioning
confidence: 99%